2022
DOI: 10.3389/fpubh.2022.924132
|View full text |Cite
|
Sign up to set email alerts
|

Do private health providers adhere to National Tuberculosis Guideline while assigning treatment outcome? Findings from a lower middle-income country

Abstract: BackgroundTreatment success rate is an important indicator to measure the performance of the National Tuberculosis Program (NTP). There are concerns about the quality of outcome data from private facilities engaged by NTP. Adherence of private providers of tuberculosis care to NTP guideline while assigning treatment outcomes to patients is rarely investigated. We aimed to determine whether Lagos private for-profit (PFP) and private not-for-profit (PNFP) facilities adhere to domestic TB guideline while assignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some recent studies have explored solutions to the system challenges identified such as inconsistent implementation of NTP guidelines, uncoordinated referrals, and lack of trust among partners. A study from Nigeria has recommended making less bulky and more precise NTP guidelines available at all levels of care, as well as training intensification for PPs to improve adherence (96). In another study, a Hub and Spoke model improved the referral system and uptake of GeneXpert testing after a coordinated engagement of private laboratories (97).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have explored solutions to the system challenges identified such as inconsistent implementation of NTP guidelines, uncoordinated referrals, and lack of trust among partners. A study from Nigeria has recommended making less bulky and more precise NTP guidelines available at all levels of care, as well as training intensification for PPs to improve adherence (96). In another study, a Hub and Spoke model improved the referral system and uptake of GeneXpert testing after a coordinated engagement of private laboratories (97).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the disruption in TB care services might result in insufficient treatment for numerous co-infected individuals, potentially contributing to preventable deaths. This concern is particularly pronounced in LMICs, where healthcare services are often limited and of lower quality [ 40 , 41 ]. Additionally, the decrease in discovered cases of TB could contribute to a lower total number of identified co-infected patients.…”
Section: Discussionmentioning
confidence: 99%